The Beneficial Effects of Doxycycline, An Inhibitor of Matrix Metalloproteinases, on Sulfur Mustard-Induced Ocular Pathologies Depend on the Injury Stage. (August 2014) - Horwitz, Vered; Dachir, Shlomit; Cohen, Maayan; Gutman, Hila; Cohen, Liat; Fishbine, Eliezer; Brandeis, Rachel; Turetz, Joseph; Amir, Adina; Gore, Ariel; Kadar, Tamar
Abstract Purpose: Sulfur mustard (SM) induces acute ocular lesions, including erosions and inflammation that may be followed by delayed injuries expressed by epithelial defects and neovascularization (NV). Based on the matrix metalloproteinases (MMPs) activity, we evaluated the clinical and biochemical effects of topical treatment with doxycycline, an MMP inhibitor, targeted to the various injury stages. Methods: Rabbit eyes were exposed to SM vapor. A clinical follow-up was carried out up to 2 months. Tear fluid and cornea samples were collected at different time points for measurements of MMPs activity by zymography. Efficacy of a post-exposure topical doxycycline (2 mg/ml in phosphate buffer saline, ×4/d), targeted to the different phases of the clinical injury, was evaluated. Results: Elevated MMP-9 and MMP-2 activities were found in all corneas during the acute injury and in vascularized corneas during the delayed pathology. In the tear fluid, high MMP-9 activity and negligible MMP-2 activity were found in all the exposed eyes until after the appearance of the delayed pathology symptoms. Prolonged doxycycline treatment reduced MMP-9 activity in the tear fluid. During the acute phase, doxycycline treatment reduced corneal MMP-9 activity and the severity of the injury. Targeting the delayed pathology, doxycycline was clinically efficient only when treatment began before NV appearance. Conclusions: This in vivo study showed the involvement of MMP-9 and MMP-2 during different phases of the SM-induced ocular injury, and the potential of doxycycline treatment as a post exposure measure for reducing the acute injury and as a preventive therapy for ameliorating the delayed pathology. The tear fluid provided a non-invasive method for continuous follow-up of MMPs activity and revealed additional beneficial aspects of injury and the treatment.